Congruency of resources and demands and their effects on staff turnover within the English health care sector. Issue 3 (24th March 2018) - Fletcher, Luke; Carter, Matthew; Lyubovnikova, Joanne
Abstract : This study examines, at the organizational level, the congruency between job demands and resources and their effects on staff turnover within the English health care sector. Polynomial regression analyses conducted on 164 acute hospitals trusts found support for the predictions that organizations with congruent levels of resources and demands would have relatively low staff turnover whereas those with incongruent levels would have relatively high staff turnover. Overall, the study indicates that individual job design should be considered within a broader organizational design perspective. Practitioner points: We examined the organizational‐level relationships between job demands, job resources, and staff turnover within the English health care sector. Organizations comprised of many highly demanding jobs should offer higher levels of resources to help retain staff. However, some organizations may still see relatively high levels of staff turnover even after offering higher levels of resources. Conversely, some may see low levels of staff turnover, yet poor motivation and performance. Therefore, influencing levels of demands rather than simply offering more resources is important in these contexts.